THE COLLAGEN DIET : A 28-Day Plan for Sustained Weight Loss, Glowing Skin, Great Gut Health, and a Younger You - Axe, Josh, Dr. (New York : Little, Brown Spark, 2020)
This book explains how to lose weight, prevent disease, improve your digestion, and renew your youth by taking advantage of dietary collagen. Includes meal plan, recipes, and advice. Dietary collagen provides a unique blend of amino acids and other compounds, making it critical for everyone, including infants, young children, the elderly, athletes, pregnant women, new mothers, and adult men and women. Simply put: When we don't get enough of the beneficial compounds found in collagen-rich foods, we experience more injuries, chronic aches and pain, digestive issues, and other symptoms associated with aging. And most people don't get enough. Collagen is the missing ingredient that can help all of us live longer, healthier, more vital lives. This book describes how collagen helps maintain the structure and integrity of almost every part of the body. You'll learn how your skin, hair, nails, bones, disks, joints, ligaments, tendons, arterial walls, and gastrointestinal tract all depend on the consumption of collagen-rich foods.
"With 70+ recipes"--Cover.
Includes bibliographical references and index.
Keywords: High-protein diet; Collagen -- Therapeutic use; Nutrition; Diet therapy